2020
DOI: 10.1186/s43141-020-00092-0
|View full text |Cite
|
Sign up to set email alerts
|

Bioprocess and genetic engineering aspects of ascomycin production: a review

Abstract: Background Ascomycin is a highly valuable multifunctional drug which exhibits numerous biological properties. Being an immunosuppressant, it is known to prevent graft rejection in humans and has potential to treat varying skin ailments. Its derivatives represent a novel class of anti-inflammatory macrolactams. But the biosynthetic machinery of ascomycin is still unclear. Main body of the abstract Due to the structural complexity, there occurs difficulty in its chemical synthesis; therefore, microbial producti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Ascomycin production, strain Streptomyces hygroscopicus var. ascomyceticusis studied well and previous scientific reports concluded that wild strain produced ascomycin in a very little amount; therefore, various yield improvement techniques are applied [19].…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Ascomycin production, strain Streptomyces hygroscopicus var. ascomyceticusis studied well and previous scientific reports concluded that wild strain produced ascomycin in a very little amount; therefore, various yield improvement techniques are applied [19].…”
Section: Resultsmentioning
confidence: 98%
“…Ascomycin (FK520),(Fig. 3),was initially referred to as FR-900520 and isolated from S. hygroscopicus KK317 in 1962 [19]. It was due to the high effectiveness of an orally used cyclosporin A that is a cyclic peptide accompanying 11 amino acids, which led to the discovery of this novel class of compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Extraction of DNA from the different environments is followed by a metagenomic approach. Usually, there are two commonly applied methods to screen the construction of the metagenomic library, sequence‐based screening, and function‐based screening 38–40. Sequence‐based screening has the advantage of conserved sequence similarity assessment and functional gene annotation through online databases 41, 42.…”
Section: Trends and Strategies In Enzyme Engineering For Enzymatic Sy...mentioning
confidence: 99%
“…ascomyceticus ATCC 14891 [ 1 ]. Because of its specific structure, FK520 exhibits diverse biological and pharmacological activities, including antifungal [ 2 ], antimalarial [ 3 ], immunosuppressive [ 4 ] and anticonvulsive effects [ 5 ]. Therefore, FK520 has shown broad application prospect in the clinical treatment of organ transplant rejections, skin diseases and autoimmune diseases [ 2 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%